Karakter Agronomi Galur Padi Dihaploid Asal Kultur Antera Hasil Persilangan Three Way Cross - Syafii, Mohammad; Sapta Purwoko, Bambang; Saraswati Dewi, Iswari; Bayuardi Suwarno, dan Willy (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2018)
Anther culture is useful tool in rice breeding. The technique shortens the time to obtain full homozygous plant in just one generation. Information related to genetic variability among the regenerants is important for further analysis including selection activities. The objective of this study was to analyze agronomic character variability and yield potential among doubled-haploid lines (DH0) derived from anther culture. This study was carried out in Center for Agricultural Biotechnology and Genetic Resources Research and Development (BB Biogen) from October 2016 to February 2017. The experiment was arranged in randomized complete block design (RCBD) with three replications. Forty eight doubled haploid lines derived from anther culture and three check varieties were evaluated. The results showed high genetic variability as well as broad sense heritability (more than 90%) for all variables tested. Several lines showed superior agronomic characters compared to check (Ciherang, Inpari 18, Inpago 10). Anther culture could generate high genetic variability for further selection.Keywords: anther culture, broad sense heritability, haploid technology